2012
DOI: 10.1149/2.049301jes
|View full text |Cite
|
Sign up to set email alerts
|

Composite ‘Layered-Layered-Spinel’ Cathode Structures for Lithium-Ion Batteries

Abstract: The concept of embedding a spinel component in high capacity, composite xLi2MnO3•(1−x)LiMO2 (M = Mn, Ni) ‘layered-layered’ structures to improve their electrochemical properties and cycling stability has been exploited. In this paper, we report the preparation and electrochemical characterization of three-component ‘layered-layered-spinel’ electrodes, synthesized by lowering the lithium content of a parent ‘layered-layered’ 0.3Li2MnO3•0.7LiMn0.5Ni0.5O2 material while maintaining a Mn:Ni ratio of 0.65:0.35; suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
87
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(89 citation statements)
references
References 38 publications
2
87
0
Order By: Relevance
“…For example, cations such as Al, 14,15 21 resulting in improved cycling performance. For LMR-NMC cathode materials, earlier studies attempted a similar substitution strategy with cations such as Al, 22,23 Cr, 24 Mo, 25 and Mg 26,27 and determined the changes in morphology, structure, and electrochemical performance. However, they focused only on the apparent electrochemical properties of LMR-NMC, such as first-cycle irreversible capacity, cycle capability, and rate performance, and thus, the effect of cation substitution on voltage fade in LMR-NMC cathodes remains unclear.…”
mentioning
confidence: 99%
“…For example, cations such as Al, 14,15 21 resulting in improved cycling performance. For LMR-NMC cathode materials, earlier studies attempted a similar substitution strategy with cations such as Al, 22,23 Cr, 24 Mo, 25 and Mg 26,27 and determined the changes in morphology, structure, and electrochemical performance. However, they focused only on the apparent electrochemical properties of LMR-NMC, such as first-cycle irreversible capacity, cycle capability, and rate performance, and thus, the effect of cation substitution on voltage fade in LMR-NMC cathodes remains unclear.…”
mentioning
confidence: 99%
“…1(c), except for Sample S1, all other samples exhibit superlattice reflection peaks that belong to the ordering of LiMn 6 units in monoclinic (C2/m) Li 2 MnO 3 -like components and can be attributed to Li and Mn cation ordering in the transition metal layers. 7,11,16,23,24 Selected segments (35-39°, 43-45°, and 62-70°) of the XRD patterns show the presence of an impurity phase, Ni 6 MnO 8 [ Fig. 1(d-f )], which has a lattice parameter of ³0.83 nm.…”
Section: Electrochemical Testsmentioning
confidence: 99%
“…6 Thackeray et al imported a new layered phase into the previous layeredspinel structure and synthesized "layered-layered-spinel" composite cathode structures with excellent cycle stability. 7,8 Lee et al introduced elemental Co into the layered-spinel composite material and applied ex-situ X-ray diffractometry (XRD) to analyze phase transformations in the charge-discharge process. They found that the layered phase may transform into a cubic-spinel phase and the cubic-spinel phase can transform to a tetragonal phase during discharge.…”
Section: Introductionmentioning
confidence: 99%
“…So, it is necessary to find an new electrode material with high lithium diffusion coefficient for improving the electrochemical performance of anode material at high current densities. Monoclinic Li 2 TiO 3 , a layered material with a three-dimensional path for Li ions diffusion, has been reported to be capable of stabilizing the structure of high-capacity cathode materials such as LiMnO 2 , LiCrO 2 and LiNiO 2 [14][15][16]. However, the poor electrical conductivity, on the order of 10 À7 S cm À1 at 400 K, prohit its use as a electrode material [17].…”
Section: Introductionmentioning
confidence: 99%